Determination of impact ionization parameters for low gain avalanche detectors produced by HPK. (1st October 2022) - Howard, A.; Cindro, V.; Hiti, B.; Kramberger, G.; Kljun, Ž.; Mandić, I.; Mikuž, M.
Abstract: A set of unirradiated Low Gain Avalanche Detectors from Hamamatsu Photonics from the HGTD prototype 2 run for the upgrade of experiments at the High Luminosity Large Hadron Collider were used to determine the impact ionization parameters for silicon, particularly in the electric field range of ∼30 V/μm which is of interest for LGADs. The parameters' dependence on temperature was also determined. Their validity on irradiated sensors up to 2.5·10 15 cm -2 was also tested and found to be acceptable at low biases but further work should be done to determine the dependence on fluence.